2012
DOI: 10.1155/2012/980284
|View full text |Cite
|
Sign up to set email alerts
|

Corn and Soybeans in a Strip Intercropping System: Crop Growth Rates, Radiation Interception, and Grain Yield Components

Abstract: Crop growth rates (CGR), radiation interception (IPAR), yields, and their components were determined in two crops monocultures (using one corn and two soybean genotypes) and in intercropped "strips," during three growing seasons. Corn yield in the strips significantly increased in the three seasons (13-16%) as compared to that in the monocultures. This response was due to increased yield in corn plants of the border rows of the strips, which was highly correlated to an increased IPAR, allowing high CGR at crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
1
12
0
7
Order By: Relevance
“…The bush bean Rows 2 to 5 showed on average a slightly lower, but not statistically different, pod dry matter than monocropped bush bean. These results are in line with other studies that showed a yield decline in the first row of soybean next to maize (Ghaffarzadeh et al, 1994; Iragavarapu and Randall, 1996; Verdelli et al, 2012). These studies and a more detailed study addressing soybean yield in each row of a narrow (four rows wide) strip intercropping of corn–soybean–oat (Jurik and Van, 2004) found an increasing soybean yield with the farther the distance from the maize strip.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The bush bean Rows 2 to 5 showed on average a slightly lower, but not statistically different, pod dry matter than monocropped bush bean. These results are in line with other studies that showed a yield decline in the first row of soybean next to maize (Ghaffarzadeh et al, 1994; Iragavarapu and Randall, 1996; Verdelli et al, 2012). These studies and a more detailed study addressing soybean yield in each row of a narrow (four rows wide) strip intercropping of corn–soybean–oat (Jurik and Van, 2004) found an increasing soybean yield with the farther the distance from the maize strip.…”
Section: Resultssupporting
confidence: 93%
“…The often reported higher resource‐use efficiency of intercropping systems (e.g., Willey, 1990; Rodrigo et al, 2001; Zhang and Li, 2003) combined with the facilitation of mechanized management may offer promising advantages to face the current challenges of the agricultural production in the NCP (Munz et al, 2014). Most often strip‐intercropping systems comprise a taller C4 species and a smaller legume, for example, predominantly in the United States and Argentina maize is strip‐intercropped with soybean (Ghaffarzadeh, 1999; Verdelli et al, 2012). In the NCP, there are numerous narrow‐strip intercropping combinations, for example, wheat and cotton (Zhang et al, 2008), wheat ( Triticum aestivum L.) and soybean [ Glycine max (L.) Merr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The light interception could be more available at wider interrow spacing than that of close interrow distance [ 20 – 22 ]. Intensified interplant competition for factor of light interception might influence dry matter yield of intercropped maize ears [ 23 ] because maize yield was linearly correlated with photosynthetic output [ 19 ]. If row spacing were increased in intercropping, photosynthetic activity of forage could be enhanced [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be the reason of competition between redgram in sole crop for light interception, nutrient and moisture. But, intercropping with short duration and shorter legume crops shows anidation effect with redgram by wider space availability between the each four rows of redgram and results increased growth of redgram in border rows by receiving more light and high soil moisture and nutrients without any competition and attained more growth rate (Verdelli et al, 2012).…”
Section: Dry Matter Productionmentioning
confidence: 99%